Implementation of the Direct Method to Improve Vocabulary Mastery in Arabic Language Learning for Tenth Grade Students at State Islamic Senior High School 3 Medan (MAN 3 Medan) - Rabiatun Adawiah; Kamalia Kamalia (Jurnal Eduslamic, 2026)
This study was motivated by the low level of Arabic vocabulary mastery among students in Class X 10 at State Islamic Senior High School 3 Medan, which was caused by teaching methods that still relied on lecturing, memorization, and translation. This made it difficult for students to understand the meanings of new vocabulary words. This study aims to improve students’ mastery of Arabic vocabulary through the application of the direct method. The method used was Classroom Action Research (CAR), conducted in two cycles. Each cycle consisted of four stages: planning, implementation, observation, and reflection. Data collection instruments included learning outcome tests (pre tests and post tests) and observation sheets for teacher and student activities. There was an increase in the percentage of students achieving learning mastery from 42% in Cycle I to 79% in Cycle II. Students’ average scores also increased from 71.25 to 85. It can be concluded that the direct method is an effective method for improving Arabic vocabulary mastery among students in Class X-10 at State Islamic Senior High School 3 Medan.